Oil qualities and physicochemical properties of two African crickets (Scapsipedus icipe and Gryllus bimaculatus) - Murugu K Dorothy; Arnold N Onyango; Alex K Ndiritu; Dorothy N Nyangena; Isaac M Osuga; Xavier Cheseto; Sevgan Subramanian; Sunday Ekesi; Chrysantus M Tanga (PANGAEA, 2024)
Globally, there is an increasingly important focus on the exploration of sustainable locally produced oils with better biocompatibility and enhanced performances in biomedical applications. Though crickets are rich source of lipids, there is limited research focus on the quality of these oils. This study evaluates oil qualities of two cricket species: the African cricket Scapsipedus icipe Hugel and Tanga and the two-spotted field cricket Gryllus bimaculatus De Geer. The physicochemical properties of the oils were determined using standard analytical methods, while fatty acid analysis was performed using gas chromatography-mass spectrometry. Oxalates and phytates were determined using high performance liquid chromatography, while tannins and total polyphenols were determined using spectrophotometry. Our results demonstrated that both cricket oils had similar physicochemical properties. Peroxide, saponification and acid values ranged between 1.92-2.49mEqO2/Kg, 234-246mgKOH and 1.10-2.19mgKOH, respectively. Both crickets are rich sources of essential omega-3 fatty acids (Eicosapentaenoic, Docosahexaenoic, and linolenic), and omega-6 fatty acid (linoleic). Palmitic (23.89-31.18%), and oleic (10.94-11.4%) were the most predominant saturated and monounsaturated fatty acids. Phytochemical levels ranged between 0 - 97mg/100g. The increasingly growing demand for the use of natural oil sources in the field of pharmaceutical, cosmetic and food industries, provide a unique opportunity for cricket oils to be considered as innovative market-driven and sustainable high-valued alternative products.